ANALISIS EFISIENSI TENAGA KERJA USAHATANI CABE RAWIT (Capsicum frutescens L) DI KELURAHAHAN GUNTUNG TINGGI KECAMATAN BATULICIN KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Fitri Mahyudi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
This research conducted to know ; level of labour efficiency of chili farm effort. Method used survey with observation technique, where farmer follow the example of taken at sensus modestly as 10 farmer. Result of research obtained by storey;level of productivity equal to 10.267,48 kg/ha. Distribution of external labour family (TKLK) 74,04% and family labour (TKDK) 62,70% from totalizeing the labour effusing. Mount efficiency of labour from facet of labour productivity obtained value 9,73 kg/HKO, from facet labour Productivity Indek obtained Rp 687.755,68/HKO.